Analisis Perilaku Sosial dalam Materi Pendidikan Agama Islam di HM Al-Mahrusiyah Putri Lirboyo Kediri - Deagita, Nisa' (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2023)
This research relates to behavior patterns by studying one scientific field of religion through two different approaches. Based on this background, the researcher categorizes the research focus as follows: (1) What are the forms of social behavior in Madrasah Diniyah? (2) What is the form of social behavior in the Madrasah Tsanawiyah Formal? (3) What are the factors of social behavior gaps in Madradah Diniyah and Madrasah Tsanawiyah Formal? Albert Bandura's theory forms thinking ideas with social learning theory and creates continuity based on reciprocal determinism, referring to cognitive, behavioral, and environmental determinants approaches. This type of qualitative research with a phenomenological approach. Data collection techniques through interviews, observation, and documentation techniques. The process of data analysis with data reduction techniques. This research produced results in (1) forms of social behavior in Madrasah Diniyah and (2) forms of social behavior in Madrasah Tsanawiyah based on behavioral patterns of attention, retention, reproduction, and motivation. (3) factors of gaps and the formation of social behavior in both types of Madrasah Diniyah and Madrasah Tsanawiyah.